Multiple glutathione disulfide removal pathways mediate cytosolic redox homeostasis - Morgan, Bruce; Ezeriņa, Daria; Amoako, Theresa N. E.; Riemer, Jan; Seedorf, Matthias; Dick, Tobias P. (Nature chemical biology, 2013)
Quantification of cytosolic glutathione redox potential leads to the discovery that the ABC-C transporter Ycf1 rapidly transports oxidized glutathione (GSSG) into vacuoles and whole-cell GSSG should not be used as a proxy for cytosolic GSSG.
Published: 16 December 2012
Gesehen am 07.06.2021